Perbaikan Kualitas Untuk Menurunkan Tingkat Cacat Produk Di Konveksi Rajut Garut - Maulana, Irsan; Chandrahadinata, Dody (Jurnal Kalibrasi, 2024)
Quality is a consumer's perspective on a product regarding all aspects that consumers need, one of which is freedom from product defects. The level of defective sweater products at the Garut Knitting Convection still exceeds the specified limits, so it is necessary to conduct a study regarding quality control. The aim of this research is to determine the types of defects and factors that cause defects in sweater products, and to design improvements so that they can minimize the level of defects. The approach used utilizes the defining, measuring, analyzing, improving and controlling (DMAIC) stages of the Six Sigma method, and is elaborated with quality control tools. The research results show the measurement results of the type of sweater defects that are often found, namely the type of stain defect. Next, an analysis was carried out using a cause and effect diagram on the type of stain defects so that several factors were obtained, and the risk of failure for each identified factor was measured and produced material factors with the potential for dirty raw materials with the largest risk priority number (RPN). Meanwhile, further analysis was carried out on the greatest potential risk of failure so that an improvement plan could be obtained to reduce the level of defects in sweater products by adding yarn cleaning tools to be processed, as well as preparing SOP’s for using yarn cleaning tools on knitting machines. The results of implementing improvements that have been carried out have proven to be able to reduce the level of loss in sweater products by 4.37%.